Argumentation Frameworks with Attack Classification. (27th January 2023) - Vassiliades, Alexandros; Flouris, Giorgos; Patkos, Theodore; Bikakis, Antonis; Bassiliades, Nick; Plexousakis, Dimitris
Abstract: Abstract argumentation frameworks (AAFs), introduced by Dung (1995, Artif. Intell., 228, 321–357), enabled a new way of reasoning with arguments, which does not take into account the internal structure of arguments but only how they are related to each other. The only form of relation considered in AAFs is a binary attack relation on the set of arguments. From the definitions of acceptability semantics of AAFs, it is obvious that attacks actually have a dual role: on the one hand, they generate conflicts; on the other hand, they can defend other arguments from attacks. In this paper, we propose a framework, where the modeller can explicitly specify the role of each attack. For this purpose, we define a set of conflict-generating attacks ${\mathcal {R}_{C}}$ and a set of defending attacks ${\mathcal {R}_{d}}$, as well as a family of semantics that considers the role of each attack while determining which arguments are attacked, which are defended and which will be included in each extension. We study the formal properties of the proposed framework and semantics, show that our framework is a generalization of AAFs and assess its semantics against a set of principles. Finally, we present a web application that provides an interface for creating custom argumentation frameworks and uses ASP to compute their extensions.